Chinese Agricultural Technology Aid in Africa - Li, Xiaoyun. author. aut Link
XXIX, 259 p. 1 illus.
Keywords: The book presents findings of anthropological studies conducted by researchers from Agricultural Technology Demonstration Center in a number of African countries, including Zimbabwe, Ethiopia, Tanzania, and Mozambique. The aim of these ethnological studies is to understand the Center’s experience in these countries as well as the way it works in terms of institutional arrangement, interaction between Chinese and local staff and technology transfer. A basic contention of the book is that insofar as these Centers showcase China’s achievements in domestic development for purpose of sharing the country’s experiences with host countries, what they do essentially points toward a new and innovative approach to foreign aid.